2016
DOI: 10.1007/s00792-016-0820-3
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of gene cassettes and the abundance of the class 1 integron-integrase gene in sediment polluted by metals

Abstract: The integron-gene cassette system has typically been associated with antibiotic-resistant pathogens. However, the diversity of gene cassettes and the abundance of class 1 integrons outside of the clinical context are not fully explored. Primers targeting the conserved segments of attC recombination sites were used to amplify gene cassettes from the sediment of the Mina stream, which exhibited a higher degree of stress to metal pollution in the dry season than the rainy season. Of the 143 total analyzed sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…ARGs-cassettes represented a small proportion of the total of the cassette-related ORFs. This observation is consistent with other studies reports that resistance cassettes abundance is relatively low compared to their diversity [6,37]. Additionally, known ARGs-cassettes still represent a small fraction of the environmental resistance pool, despite the progressive increase in related databases [38].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…ARGs-cassettes represented a small proportion of the total of the cassette-related ORFs. This observation is consistent with other studies reports that resistance cassettes abundance is relatively low compared to their diversity [6,37]. Additionally, known ARGs-cassettes still represent a small fraction of the environmental resistance pool, despite the progressive increase in related databases [38].…”
Section: Discussionsupporting
confidence: 92%
“…Genomic and metagenomic studies with different hosts and environments have demonstrated that gene cassettes are extremely diverse, comprising many unknown functions [36]. Among the identified ORFs, general metabolic processes, e.g., oxidation-reduction, were more frequent, as reported elsewhere [37].…”
Section: Discussionsupporting
confidence: 52%
“…Oliveira-Pinto et al. ( 2016 ) isolated an intI gene cassette related to Nitrospirae from a metal-rich stream, and Goltsman et al. ( 2009 ) identified both integrase and ARGs on chromosomes of Nitrospirae strains isolated from acid mine drainage.…”
Section: Resultsmentioning
confidence: 99%
“…One such bioindicator gene, the class 1 integrase ( intI1) (Gillings et al, 2015) has been shown to be present in many anthropogenic samples including human stool (Phongpaichit et al, 2008), wastewater treatment plants (WWTPs, Ma et al, 2013) and surrounding airborne aerosol emissions (Li et al, 2016), river sediment near WWTP effluent discharge lines (Karkman et al, 2016), ponds (M. Wang et al, 2016), landfill sites (Sun et al, 2016), untreated hospital effluents (Spindler et al, 2012), many animal hosts (Colello et al, 2015; Lluque et al, 2015), and in sediment and soils polluted or treated with metals (Oliveira-Pinto et al, 2016) and antibiotics (Cleary et al, 2016). The intI1 gene or a similar maker could eventually play a role in regulatory environmental monitoring of ARGs (Berendonk et al, 2015).…”
Section: Introductionmentioning
confidence: 99%